Topical Use of Saussurea costus (Falc.) Lipsch. (Qost) Oil in Pediatric Nocturnal Enuresis in Comparison with Sesame Oil, A Randomized Double-Blind Clinical Trial - Reza Ilkhani; Mojtaba Bigdeli; Masoumeh Mohkam; Nezhat Shakeri; Shirin Fahimi Tafreshi; Seyyed Mohammad Taghi Hosseini Tabatabae; Monireh Sadat Motaharifard (Tehran University of Medical Sciences, 2021)
Nocturnal enuresis is one of the most common chronic problems of childhood. It has a significant effect on health and quality of life of children and their families. Despite pharmacological treatments, enuresis in most children relapses after the medication is discontinued. Also available drugs have many side effects that limited their uses. So, we compared the effect of topical use of Saussurea costus (Falc.) Lipsch. (Qost) oil as a Persian Medicine product on pediatric nocturnal enuresis in a parallel randomized double blinded study. Eighty-two patients aged 5 to 15 years who were diagnosed as monosymptomatic nocturnal enuresis were allocated to receive costus oil or sesame oil topically below the navel twice a day for 4 weeks. Patients were evaluated prior to and following end of the study in terms of frequency of enuresis and any observed adverse events. The results were evaluated with valid PLUTSS questionnaire. For evaluation, Chi-square and Fisher's exact tests, Mann-Whitney and Wilcoxon tests were used. Significant p value was < 0.05. A significant decrease in mean scores of the questionnaires was noted in both groups. The results before and after the intervention were significantly different in both groups, but there was no statistically significant difference between the intervention and control groups. At the end of the 4th week, the frequency and volume of enuresis showed a 46.2 percent reduction in costus oil group and a 25.5 percent reduction in sesame oil group. According to this study, the response rate based on PLUTSS questionnaire in costus oil group is 74.5%; while in the sesame oil group is 69%. No drug side effect was noticed in this study. Based on the results of this study, costus oil is effective in children with monosymptomatic nocturnal enuresis; however, there is no significant difference between costus oil and sesame oil.